Utilizing digital story writing as a pedagogical approach to foster Artificial Intelligence (AI) literacy in students - Rachman, Dzul; Khatimah, Khusnul; Siswa, Taghfirul Azhima Yoga; Putri, Azzahra Namira; Sidiq, Reza June (Psychology, Evaluation, and Technology in Educational Research, 2024)
Artificial intelligence literacy is a comprehensive set of skills, knowledge, and ethical considerations that are essential for the responsible and efficient integration of artificial intelligence into daily activities. Nevertheless, there is currently a lack of a comprehensive framework that enables the comprehensive analysis of all aspects of digital stories in a broad sense. By providing an analytical framework that allows the authors to evaluate digital stories generated by students from a variety of perspectives, this study endeavors to address this gap. The authors employ this paradigm to illustrate how learners can leverage the diverse modalities of digital tales to improve their comprehension of the curriculum, while simultaneously creatively expressing their identities and perspectives. Throughout their involvement in AI learning and digital story writing activities, the interviews with students were designed to investigate their perspectives on learning.